The Effect of Burnout on the Turnover Intention: A Study on 5 Star Hotels in Famagusta - Tanözü, Bahar Afet (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
Servicing is the one of the most stressful occupations in the 21st century. Hotel employees take a significant role in servicing in hospitality and tourism sector. Being in service sector mainly centred on clients’ problems, and facing and working with people is backbreaking. The emotional pressure, long working hours and shifts, relations and communications with colleagues and managers, active working for long hours, work ambiguity or overloaded work are some of the reasons causes burnout in certain time in hospitality among hotel employees. Burnout is a state of emotional, physical, and mental exhaustion caused by excessive and prolonged stress. Burnout syndrome consists of three basic dimensions: emotional exhaustion, depersonalization and personal accomplishment, and these dimensions express the changes in the life of the individual experiencing burnout. Burnout closely concerns and affects individuals, businesses and organizations. Hotel businesses and employees are also one of the sectors closely affected. In hospitality and tourism sector work conditions and laws unsatisfactory in Northern Cyprus. Compered to developed countries in Famagusta region in Northern Cyprus hotels have worse conditions for employees. Furthermore lack of governmental controls, inspections causes illegal shifts and overloaded work, which are non-ethical work conditions, affects employees’ emotions and physical conditions negatively. The aim of the current study is to consider hotel employees’ burnout level affects on turnover intention. This study conducted on five-star hotel employees in Famagusta. Two fıve-star hotels located in Famagusta region. 280 hotel employees voluntarily participated in this research. 204 of participants totally complete the questionnaires. According to the ANOVA test p-value result (p<0.05=0.005) an important positive relationship found between burnout and turnover intention. Burnout affects hotel employees’ turnover intentions. Keywords: hotel employees, burnout, turnover intention, Northern Cyprus, hotels, emotional exhaustion, depersonalization, personal accomplishment, Famagusta, five stared hotels

ÖZ: Hizmet sektörü, 21. yüzyılın en stresli mesleklerinden biridir. Otel çalışanları, otelcilik ve turizm sektöründe hizmet vermede önemli rol oynamaktadır. Hizmet sektöründe olmak, esas olarak müşterilerin sorunları merkezli olduğundan insanlarla yüz yüze kalmak ve çalışmak çalışanlar için yıpratıcıdır. Duygusal baskı, uzun çalışma saatleri ve vardiyalar, meslektaşlar ve yöneticilerle ilişkiler ve iletişim, uzun saatler aktif çalışma, iş belirsizliği veya aşırı çalışma, otel çalışanlarında belirli zamanlarda tükenmişliğe neden olan etkenlerden bazılarıdır. Tükenmişlik sendromu duygusal tükenme, duyarsızlaşma ve kişisel başarı olmak üzere üç temel boyuttan oluşmaktadır. Duygusal tükenme, duyarsızlaşma ve kişisel başarı tükenmişliği deneyimleyen kişilerin hayatlarındaki değişimlerin şekilleri ifade eder. Tükenmişlik bireyleri, işletmeleri ve kuruluşları yakından ilgilendirir ve etkiler. Otel işletmeleri ve çalışanları da yakından etkilenen sektörlerden biridir. Kuzey Kıbrıs'ta konaklama ve turizm sektöründe çalışma koşulları ve kanunlar yetersiz kalmaktadır. Ayrıca gelişmiş ülkelere kıyasla Kuzey Kıbrıs Gazimağusa bölgesindeki oteller çalışanlar için daha kötü koşullara sahiptir. Bahsedilen olumsuz şartlar; devlet kontrollerinin olmaması, denetimler, etik dışı çalışma koşulları olan yasa dışı vardiyalar ve çok uzun çalıma saatleridir. Tüm bu olumsuz şartlar çalışanların duygularını ve fiziksel koşullarını olumsuz yönde etkilemektedir. Bu çalışmanın amacı, otel çalışanlarının tükenmişlik düzeylerinin işten ayrılma niyetine etkilerini ele almaktır. Bu çalışma Gazimağusa bölgesinde bulunan beş yıldızlı otellerde yürütülmüştür. Bölgede iki tane beş yıldızlı otel bulunmaktadır. Çalışmaya 280 otel çalışanı gönüllü olarak katılmıştır. Ancak 204 anket tamamen tamamlanmış ve kullanılabilirdi. SPSS ANOVA test, p değeri sonuçlarına göre (p<0.05=0.005) tükenmişlik ve işten ayrılma eğilimi arasında önemli ölçüde bir ilişki vardır. Tükenmişlik düzeyi otel çalışanlarının işten ayrılma eğilimlerini etkilemektedir. Anahtar Kelimeler: otel çalışanları, tükenmişlik, işten ayrılma eğilimi, Kuzey Kıbrıs, Gazimağusa, duygusal tükenme, duyarsızlaşma, kişisel başarı, beş yıldızlı oteller
Master of Arts in Marketing Management. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2021. Supervisor: Asst. Prof. Dr. Doğan Ünlücan
Keywords: Business Administration; Marketing Management; Job stress--Burn out (Psychology)--Hotel Employees--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; Personnel management--Tourism Industry--Hospitality Industry--Hotels-- --Hotel Employees--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; Employee motivation--Tourism; Job satisfaction--Tourism; Work--Psychological aspects; Employees--Attitudes; Hotel employees; burnout; turnover intention; Northern Cyprus; hotels; emotional exhaustion; depersonalization; personal accomplishment; Famagusta; five stared hotels